ETV5 reduces androgen receptor expression and induces neural stem–like properties during neuroendocrine prostate cancer development - Jongeun Lee; Jiho Park; Yunjung Hur; Dahun Um; Hyung-Seok Choi; Joonyoung Park; Yewon Kim; Jeon-Soo Lee; Kyuha Choi; Eunjeong Kim; Young Bin Park; Jae-Mun Choi; et al. (Proceedings of the National Academy of Sciences, 2025)
Neuroendocrine prostate cancer (NEPC), an aggressive subtype induced by hormone therapy, lacks effective treatments. This study explored the role of E26 transformation-specific variant 5 (ETV5) in NEPC development. Analysis of multiple prostate cancer datasets revealed that NEPC is characterized by significantly elevated ETV5 expression compared to other subtypes. ETV5 expression increased progressively under hormone therapy through epigenetic modifications. ETV5 induced neural stem–like features in prostate cancer cells and facilitated their differentiation into NEPC under hormone treatment conditions, both in vitro and in vivo. Our molecular mechanistic study identified PBX3 and TLL1 as target genes of ETV5 that contribute to ETV5 overexpression–induced castration resistance and stemness. Notably, obeticholic acid, identified as an ETV5 inhibitor in this study, exhibited promising efficacy in suppressing NEPC development. This study highlights ETV5 as a key transcription factor that facilitates NEPC development and underscores its potential as a therapeutic target for this aggressive cancer subtype.